Encapsulation of iron(III) protoporphyrin IX and tetraphenylporphyrin in metal-organic frameworks for application as heterogeneous oxidation catalysts - Dare, Nicola A (Department of Chemistry, 2019)
Two MOFs, [H2N(CH3)2][Zn3(TATB2(HCOO)]·HN(CH3)2·DMF·6H2O (1) and ZnHKUST-1 (2) (TATB = 4,4′,4″-s-triazine-2,4,6-triyl-tribenzoate) were investigated as potential hosts to encapsulate Fe(III) protoporphyrin IX (ferrihaem = Fe(III)PPIX) and Fe(III) tetraphenylporphyrin (Fe(III)TPP). Methyl orange (MO) adsorption was used as an initial model for substrate uptake in MOFs 1 and 2. MOF 1 showed good adsorption of MO (10.3 ± 0.8 mg.g-1 ) which could undergo in situ protonation upon exposure to aqueous HCl vapour. By contrast MO uptake by 2 was much lower (2 ± 1 mg.g-1 ) and PXRD indicated structural instability on exposure to water was the likely cause. Two methods for Fe(III)PPIX incorporation into 1 were investigated: soaking and encapsulation. Encapsulation was verified by SEM-EDS and showed comparable concentrations of Fe(III)PPIX on exposed interior surfaces and on the original surface of fractured crystals. SEM EDS results were consistent with ICP-OES data on bulk material (1.2 ± 0.1 mass % Fe). PXRD data showed that the framework in 1 was unchanged after encapsulation of Fe(III)PPIX. MO adsorption (6 ± 1 mg.g1 ) by Fe(III)PPIX-1 confirmed there is space for substrate diffusion into the framework, while the UV-visible spectrum of solubilized crystals confirmed that Fe(III)PPIX retained its integrity. A solid-state UV-visible spectrum of Fe(III)PPIX-1 indicated that Fe(III)PPIX was not in a µ-oxo dimeric form. Although single-crystal XRD data did not allow for full refinement of the encapsulated Fe(III)PPIX molecule owing to disorder of the metalloporphyrin, the Fe atom and pyrrole N atoms were located, enabling rigid-body modelling of the porphine core. For comparison, Fe(III)PPIX was further encapsulated in 2, forming Fe(III)PPIX-2. Reaction ABSTRACT of 2,2'-azino-bis(3-ethylbenzothiazoline)-6-sulphonic acid (ABTS) with H2O2, catalysed by Fe(III)PPIX-1 and -2 showed that Fe(III)PPIX-1 is significantly more efficient than Fe(III)PPIX-2 and is superior to solid Fe(III)PPIX-Cl due to the faster initial rate of reaction as well as the greater conversion of ABTS to ABTS●+ . Both frameworks 1 and 2 were also investigated as potential hosts to encapsulate Fe(III) tetraphenylporphyrin (Fe(III)TPP). Attempts to encapsulate Fe(III)TPP into 1 were unsuccessful, but Fe(III)TPP was successfully encapsulated into 2, forming Fe(III)TPP-2. The framework was characterised by PXRD and SEM-EDS confirmed uniform distribution of Fe(III)TPP through the framework. The loading of Fe(III)TPP determined using ICP-OES (0.604 ± 0.008 Fe mass %) agreed well with SEM-EDS data. Single crystals of Fe(III)TPP-2 were obtained and structure determination showed that the Fe(III) porphyrin was positionally disordered over three positions. The instability of Fe(III)TPP-2 in the presence of H2O resulted in it being an inappropriate choice as an oxidation catalyst. The kinetics of ABTS oxidation by H2O2 catalysed by Fe(III)PPIX-1 were further investigated. The peroxidatic activity of this heterogeneous system conforms to a rate law identical to that observed in solution with no discernible influence of particle size, suggesting that the MOF system closely mimics the solution state. The proposed rate law indicates a reaction mechanism with two possible pathways, as suggested for the same reaction in solution. The major pathway describes the coordination of H2O2 to the Fe(III) centre and subsequent formation of a high valent intermediate, while the minor pathway describes the same process preceded by ABTS coordination to the Fe(III) centre forming a six-coordinate complex. The further application of Fe(III)PPIX-1 as an oxidation catalyst was probed by investigating the catalytic oxidation of hydroquinone, thymol, benzyl alcohol and phenyl ethanol by tert-butyl-hydroperoxide ( tBuOOH). Reactions were successful and showed t1/2 values that increase with increasing substrate molecular volume.